Desempenho de indivíduos saudáveis e afásicos em uma bateria de avaliação de praxia de membros - Mantovani-Nagaoka, Joana [UNIFESP] (2009)
Apraxia is defined as a disorder of learned skilled movements in the absence of elementary motor or sensory deficits or general cognitive impairment, such as inattention to commands, object-recognition deficits and poor oral comprehension. It is generally attributed to left hemisphere brain damage, which is commonly associated to language impairments or aphasias. The purpose of the present study was to characterize the performance of healthy and aphasic adults in a battery for assessment of limb praxis, searching for the role played by demographic variables such as educational background, age and gender in this performance. Also, we aimed to compare the healthy and aphasic subjects performances in this praxis assessment. We elaborated a battery for assessment of limb praxis, composed of: object/action oral comprehension and naming tasks, object function definition and recognition tasks and recognition of transitive gestures test; likewise, the battery included tasks demanding motor execution of transitive, intransitive, pantomimed and meaningless gestures, in response to verbal command or on imitation. Fortyfour healthy subjects, without any history of brain damage, participated in this study (control group), and 28 aphasic participants, with a single left-hemisphere damage, composed the aphasic group. All subjects were submitted to a battery for assessment of limb praxis. Data showed that the gender did not influence performances on both control and aphasic groups, while the age influenced the recognition of transitive gestures, on both groups. The age also influenced the imitation of dynamic meaningless gestures in the aphasic group. Educational background, however, influenced the performances of both groups in many other tasks. Brain damage, on the other hand, interfered only in the linguistic tasks of object/action naming, object function definition and recognition. It had also interfered in the execution of more complex transitive and pantomimed gestures and in the imitation of meaningless dynamic gestures, on the aphasic group, which may be due to lexical-semantic and phonological deficits associated with aphasias. Therefore, the educational background showed to play an important role on the praxic abilitties assessed by the battery of limb praxis, on both control and aphasic group, while age and brain damage, that one only in the aphasic group, interfered in a less impactant way.